A Plant-Based Dietary Intervention for Preoperative Glucose Optimization in Diabetic Patients Undergoing Total Joint Arthroplasty. Issue 1 (January 2022) - Drost, Jennifer M.; Cook, Curtiss B.; Spangehl, Mark J.; Probst, Nicholas E.; Mi, Lanyu; Trentman, Terrence L.
Purpose. The purpose of this study was to assess the feasibility and effectiveness of a whole food plant-based diet (WFPBD) to improve day of surgery fasting blood glucose (FBG) among patients with type 2 diabetes (T2D). Patients and Methods. Ten patients with T2D scheduled for a total hip or total knee replacement were recruited. For 3 weeks preceding their surgeries, subjects were asked to consume an entirely WFPBD. Frozen WFPBD meals were professionally prepared and delivered to each participant for the 3 weeks prior to surgery. FBG was reassessed on the morning of surgery and compared with preintervention values. Compliance with the diet was assessed. Results. Mean age of subjects and reported duration of diabetes was 65 and 8 years, respectively, average hemoglobin A1c (HbA1c) was 6.6%, and 6 were women. Mean FBG decreased from 127 to 116 mg/dL ( P = .2). Five of the subjects experienced improvement in glycemic control, with an average decline of 11 mg/dL. Conclusion. A WFPBD is a potentially effective intervention to improve glycemic control among patients with T2D during the period leading up to surgery. Future controlled trials on a larger sample of patients to assess the impact of a WFPBD on glycemic control and surgical outcomes are warranted.